Supporting small and medium enterprises towards Green Economy (Ökologisches Wirtschaften - Fachzeitschrift, 2014)
In order for green business development services to be effective, market promotion on the supply and demand side is necessary. What is its role in the transition to Green Economy in emerging economies? Challenges and opportunities of this new concept are illustrated with experiences of German Development Cooperation from India.